Carnivalisation of the Russian Language in the Era of the Coronavirus Pandemic - Kupina, Natalia A. (Izvestiâ Uralʹskogo federalʹnogo universiteta. Seriâ 2, Gumanitarnye nauki, 2021)
This article studies the carnivalisation of the Russian language in the era of the coronavirus pandemic (March–early December 2020) based on extracts from media texts and live colloquial speech. The phenomenon of carnivalisation is analysed with reference to M. M. Bakhtin’s concept of carnivalisation and D. S. Likhachev’s generalisations about the folk culture of laughter. It is established that the Russian carnival is associated with will. In the situation of a new “coronavirus normality”, the language forms a layer of anxiety vocabulary, which stimulates word and meaning coinage. It is proved that mass linguistic creativity is a form of resistance to disturbing reality. The author systematises potential neologisms, nonce words, and non-standard metaphors. Word innovations act as a means of creating a comic effect, characterisation, and axiological assessment of reality, as well as a means of diagnosing the tender points of the coronavirus space and a means of psychotherapy. The author distinguishes a temporal model formed in the linguistic worldview which reflects the imperfection of the world: the extended present of the coronavirus; pre-coronavirus past; post-coronavirus future which is conceived as a desired return to the past (the slogan Вперед в будущее!). As part of the analysis, the author describes a layer of new compound word-formations with корона- as the first component. Also, she pays special attention to the interpretation of words close to the core of anxiety vocabulary (путинкулы, полный карантинец, etc.). A unique object of analysis is a group of colloquial words that replace business standards (дистанционка, удаленка, запрещенка), as well as neologisms that expand the number of derivatives of the word маска. The author points out the development of coronavirus literature and characterises new online technologies studied by literature, art, and education specialists. Finally, the article describes the axiological explosion accompanying the carnivalisation of the Russian language.